Effectiveness of Play-Based Intervention on Emotional Intelligence and Peer Interaction in Children - Acar, Zeynep; Kaya, Selin (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective:  This study aimed to investigate the effectiveness of a structured play-based intervention program in improving emotional intelligence and peer interaction among children.Methods and Materials: A randomized controlled trial was conducted with 30 children aged 6 to 10 years from primary schools in Turkey. Participants were randomly assigned to an experimental group (n = 15) that received a ten-session play-based intervention or a control group (n = 15) that received no intervention. The intervention was designed to enhance emotional recognition, regulation, empathy, and cooperative behaviors through experiential activities such as storytelling, role-play, and group games. Emotional intelligence was assessed using the Emotional Quotient Inventory: Youth Version (EQ-i:YV), and peer interaction was measured using the Penn Interactive Peer Play Scale (PIPPS). Measurements were conducted at three stages: pretest, posttest, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests in SPSS-27.Findings: The results showed significant improvements in both emotional intelligence and peer interaction in the experimental group compared to the control group over time. For emotional intelligence, repeated measures ANOVA indicated a significant time by group interaction effect, F(2, 56) = 29.74, p < .001, η² = .51. A similar significant interaction was observed for peer interaction, F(2, 56) = 25.47, p < .001, η² = .48. Bonferroni post-hoc tests revealed that improvements from pretest to posttest were significant and sustained at follow-up for both variables (p < .001), while the control group showed no significant changes.Conclusion: The findings suggest that play-based interventions are an effective and sustainable method for enhancing emotional and social competencies in children and can be integrated into educational settings to support psychological development.